PENGARUH EMPLOYEE SATISFACTION TERHADAP CUSTOMER SATISFACTION DAN CUSTOMER LOYALTY RESTORAN KELUARGA DI SURABAYA - Dion Heggie Hartanto; Indarini Indarini; Silvia Margaretha (Perpustakaan Universitas Surabaya, 2018)
s study aims to prove the effect of employee satisfaction towards customer satisfaction and customer loyalty intentions for family restaurants respondents’ in Surabaya.This type of research is causal research with quantitative approach. This study using purposive sampling approach, which is a sampling technique based on the consideration or personal judgment of researchers associated with the characteristics of the population according to the research sample. Respondents in this study amounted to 210 people. The analysis in this study using a model of SEM (Structural Equation Modeling) and processed using SPSS software version 18.0 for Windows and Amos version 22.0 for Windows for testing Measurement and Structural Model.The result of this study indicate that hypothesis 1 and 3 were supported and have positive significantly effect such as employee satisfaction has positive and significant effect on customer satisfaction, customer satisfaction has positive and significant effect on customer loyalty. For hypothesis 2 were not supported and does not have positive significantly effect that is employee satisfaction has positive and significant effect on customer loyalty.